A new testing device to simultaneously measure the mode I fatigue delamination behavior of a batch of specimens. (November 2018) - Renart, J.; Budhe, S.; Carreras, L.; Mayugo, J.A.; Costa, J.
Highlights: A test device and a method to run 6 DCB fatigue tests in parallel are detailed. The method allows testing at different levels of energy release rate and load ratios. Onset of fatigue propagation of 6 DCB specimens is determined in one run. Continuous crack growth rate curves are obtained. The onset points are determined with an accuracy of 1 cycle. Abstract: Determining fatigue onset and crack propagation curves for delamination in composites requires time-consuming test campaigns. This work presents a new test rig and its associated methodology to test several mode I specimens simultaneously in a universal testing machine. The novelty of the solution relies on being able to test several specimens at different levels of load ratio and energy release rates in a single run. The performance of the system is exemplified by measuring the complete onset and crack growth rate curves of a batch of 12 carbon fibre reinforced specimens in only two test runs.